Phase I pharmacokinetic and pharmacodynamic study of the prenyl transferase inhibitor AZD3409 in patients with advanced cancer. - Appels, N; Bolijn, M; Chan, K; Stephens, T; Hoctin-Boes, G; Middleton, M; Beijnen, J; de Bono, J; Harris, A; Schellens, J (2008)
AZD3409 is an orally active double prodrug that was developed as a novel dual prenyltransferase inhibitor. The formation of the active metabolite AZD3409 acid is mediated by esterases in plasma and cells. The aim of this phase I study was to determine the maximum tolerated dose, toxicities, pharmacokinetics and pharmacodynamics of AZD3409. AZD3409 was administered orally to patients with advanced solid malignancies using an interpatient dose-escalation scheme starting at 500 mg AZD3409 once daily. Twenty-nine patients were treated at seven dose levels. The MTD of part A was defined as 750 mg b.i.d. in the fasted state. Adverse events were mainly gastrointestinal and the severity was on average mild to moderate and reversible. The dose-limiting toxicities were vomiting, diarrhoea and uncontrolled nausea. Pharmacokinetic studies of the prodrug and the active metabolite indicated dose proportionality. Pharmacodynamic studies showed that farnesyltransferase (FTase) was inhibited at all dose levels. In conclusion, chronic oral dosing with AZD3409 is feasible and results in significant inhibition of FTase activity. Pharmacodynamic studies revealed that the maximal FTase inhibition, estimated at 49+/-11%, appeared to be reached at AZD3409 acid plasma concentrations at which the occurrence of drug-related toxicity was low. This study supports the rationale to implement biological effect studies in clinical trials with biologically active anticancer drugs to define optimal dosing regimens.